Emergency contraception: Links between providers' counseling choices, prescribing behaviors, and sociopolitical context. (December 2019) - Wagner, Brandon G.; Cleland, Kelly; Batur, Pelin; Wu, Justine; Rothberg, Michael B.
Abstract: Healthcare decisions depend on the characteristics of patients and providers. However, how these decisions are influenced by provider interpretations of biological processes and the sociopolitical context in which they work remains unclear. To answer these questions, we explore providers' prescribing of emergency contraception (EC), methods that can prevent pregnancy after sex has already occurred. Despite the consensus mainstream medical definition that pregnancy begins after a fertilized egg implants in the uterus, an alternative perspective holds that pregnancy instead begins when a sperm fertilizes an egg. How providers define pregnancy may affect their willingness to prescribe EC. However, the ability of providers to recommend treatments consistent with their understandings of medical processes may depend on the sociopolitical context in which the patient-provider interaction occurs. We test whether EC prescribing practices vary by providers' definition of pregnancy and the interaction of this definition with the sociopolitical context in which they practice. Data from U.S. medical providers were collected as part of a survey on EC knowledge and practices (N = 1308). We merged voting results from the county in which the provider practices to data on provider EC prescribing and pregnancy counseling practices. Because recent Republican party platforms have explicitly endorsed a definition of pregnancy that begins at fertilization and party advocacy frequently uses this definition, we use the county vote share for the Republican presidential candidate as a contextual measure of views that pregnancy begins at fertilization. We find a significant interaction such that providers who counsel that pregnancy begins at fertilization are significantly less likely to prescribe EC if they practice in counties with higher Republican vote shares. Our results highlight that patient access to EC may depend on both place of residence and provider views and that providers' EC prescribing may depend jointly on their understanding of pregnancy and sociopolitical context. Highlights: Provider interpretations of medical knowledge may influence care. This influence may depend on the social context on which providers practice. Two definitions of pregnancy exist, so we test emergency contraception prescribing. EC prescribing varies jointly by provider pregnancy counseling and county politics.